Landing Control Based on Energy Prediction for a Quadcopter Under External Disturbances - Nguyen, Cuong V. (Universitas Muhammadiyah Yogyakarta, 2024)
Unmanned aerial vehicles (UAVs) have recently become one of the most popular research topics. The high diversity in its uses has attracted research attention regarding structure or control capabilities. However, if the energy consumed in each mission cannot be predicted, the available flight time will pose many risks to the UAV and data security. This paper proposes a control algorithm based on predicting the remaining flight time to determine a safe landing station. Suppose the UAV cannot reach the desired destination station. In that case, it will find the nearest landing station to recharge its energy until the SoC (State of Charge) > 90%, then the UAV will continue to perform the mission until the UAV reaches the destination station. In addition, the paper uses a marker-based landing method to improve landing accuracy. The sliding mode controller (SMC) is designed to consider external disturbance factors and consider a solution to reduce chattering.